Antisocial Alcoholism in Parents of Adolescents and Young Adults With Childhood ADHD. Issue 9 (July 2020) - Molina, Brooke S. G.; Gnagy, Elizabeth M.; Joseph, Heather M.; Pelham, William E.
Objective: Test the hypothesis that alcoholism, including antisocial alcoholism, is more prevalent among mothers and fathers of children with versus without ADHD.Method: Mothers (312 ADHD group, 235 non-ADHD group) and fathers (291 ADHD group, 227 non-ADHD group) in the Pittsburgh ADHD Longitudinal Study were interviewed along with their adolescent and young adult offspring.Results: Maternal and paternal alcoholism, with and without comorbid antisociality, was more prevalent in the ADHD group. Paternal alcoholism without antisociality was only marginally higher for probands after controlling for paternal ADHD. Offspring conduct disorder comorbidity was associated with parental antisociality but not parental antisocial alcoholism.Conclusion: Our findings that 44% of proband fathers and 25% of proband mothers experienced alcohol problems with or without antisociality are further evidence of increased alcoholism prevalence in families affected by ADHD. Maternal alcoholism and antisociality are prominent contributors to this family-level vulnerability. These findings indicate the need to assess long-term offspring outcomes as a function of parental alcohol and externalizing comorbidities, and perhaps other indicators of parental alcoholism phenotype, as familial vulnerability unfolds across development.